Relationship between Knowledge and the Use of Personal Protective Equipment in Farmers with History of Goiter Disease in Kismantoro Subdistrict Wonogiri - Ahshaina Ramadhaningtiyas; Yulia Lanti Retno Dewi; Sugihardjo Sugihardjo (Masters Program in Public Health, 2021)
Background: Farmers have a great potential danger to exposure and poisoning of pesticides due to the application of occupational safety and health, which is still low because it does not use personal protective equipment (PPE). This study aimed to examine the relationship of knowledge using PPE in farmers with a history of goiter disease in the Kismantoro Subdistrict, Wonogiri Regency.Subjects dan Method: This was a cross-sectional study. Sampling techniques used purposive sampling with inclusion criteria that are willing to participate in this study, reside and become a farmer in Kismantoro Subdistrict for more than ten years, and have a history of goiter disease work actively as a farmer. The dependent variables were complete PPE and PPE masks in farmers. The independent variable was knowledgeable. Population: All farmers who were declared positively affected by goiter and recorded in the Kismantoro Subdistrict Health Center in 2020. Sample: The samples were 54 respondents. Data collection was done directly from respondents with observation techniques or observation into the field and questionnaire filling. The data were analyzed using chi-square test.Results: There was a relationship between the knowledge of farmers with a history of goiter disease with the use of complete PPE when spraying with p= 0.005 and (OR=0.77; 95%CI= 0.62 to 0.97). And there was a relationship between the knowledge of farmers with a history of goiter disease with the use of masks at the time of spraying with p= 0.002 and (OR= 6.43; 95%CI= 1.93 to 21.39).Conclusion: There is a relationship between knowledge and complete PPE and masks PPE in farmers with a history of goiter disease in Kismantoro Subdistrict, Wonogiri Regency.Keywords: knowledge, the use of PPE complete, the use of PPE mask.Correspondence: